Obstetric-associated lower urinary tract injuries: a single-center study - Chaudhari, Sandipkumar; Patel, Jimitkumar; Patel, Priyanshu; Chaudhary, Naresh; Chaudhary, Sonalben; Choudhary, Bhooraram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Urinary tract injury is a known complication of obstetric and gynecologic surgery. Intraoperative identification of injury permits prompt repair and potentially lessens postoperative sequelae including patient morbidity and cost. Delayed diagnosis of urinary tract injuries can result in physical complications beyond the site of the injury, such as genitourinary fistula formation, renal injury, sepsis, death, and psychosocial dysfunction. Methods: We describe the management of 27 patients with such injuries, including their demographic profile, associated factors, and complications at a tertiary institution in a retrospective study from February 2013 to March 2021. Results: Bladder injuries were the most common (81.5%), mostly occurring during emergency cesarean delivery, with previous cesarean delivery and adhesions being risk factors. A primary repair was attempted at the referring institution in 18.5% of cases. Repair at the tertiary institution was mostly performed by consultants (66.7%). Conclusions: Early recognition and primary repair are associated with fewer complications.